How best to incorporate conjunctive water management into international water law: legal amendment, instrument coupling, or new protocol adoption? - Ibrahim, I. A.; Lautze, Jonathan F. (Springer, 2023)
International water conventions—e.g., the 1997 United Nations Convention on the Non-Navigational Uses of International Watercourses—include positive but insufficient focus on groundwater and its interaction with surface water. As such, a growing body of literature has proposed modifications to existing frameworks to enable consideration to surface and groundwater and their interactions. While this literature places considerable focus on coupling and amending existing legal frameworks, elaboration and evaluation of a new protocol on conjunctive water management comprises a key gap. To fill this gap, this paper seeks to answer the following question: does formulation and adoption of a new “conjunctive” protocol provide more value than existing proposals centered around modifications to existing law? This paper seeks to compare benefits associated with current proposals to strengthen the international legal framework for management of surface–groundwater interaction, vis-a-vis adoption of a new protocol on conjunctive management of transboundary freshwaters. To do so, the authors use doctrinal legal methods to analyze the existing main instruments globally assessing the degree to which they consider key interlinkages between surface water and groundwater. Then, the paper examines the concept of conjunctive water management and deduces tenets that should be pursued in shared waters to achieve this objective. To identify the preferred option to support conjunctive water management in international water law, the paper explores the degree to which existing proposals vs a new protocol enable an embrace of these tenets of conjunctive water management. The paper finds that while a new protocol may add greater value in advancing conjunctive water management, multiple options can and should be concurrently pursued. In particular, the authors argue that new protocols to the existing treaties must be adopted in combination with the amendment of the Draft Articles on the Law of Transboundary Aquifers. Benefits of doing so include more effective management of transboundary freshwater resources that are interconnected hydrologically, a less fragmented and more consistent international water regime, and ultimately more benefits accruing to the populations and environmental goods dependent on shared water resources.